2016
DOI: 10.1093/cercor/bhw278
|View full text |Cite
|
Sign up to set email alerts
|

Task and Regions Specific Top-Down Modulation of Alpha Rhythms in Parietal Cortex

Abstract: Alpha (8-12 Hz) power desynchronization is strongly associated to visual perception but has been observed in a large variety of tasks, indicating a general role in task anticipation. We previously reported in human observers that interference by repetitive transcranial magnetic stimulation (rTMS) of core regions of the dorsal attention network (DAN) disrupts both anticipatory alpha desynchronization and performance during a visuospatial attention (VSA) task. Here, we test the hypothesis that alpha desynchroniz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 50 publications
8
36
0
Order By: Relevance
“…Participants who exhibited stronger high-alpha phase synchronization also exhibited stronger lateralization of low-alpha amplitudes during attention shifting. Highalpha phase synchronization between frontal and parietal cortices could thus mediate attention-related low-alpha band suppression, similar to structural connectivity (Marshall et al, 2015a) and perturbation of frontoparietal cortex with TMS (Capotosto et al, 2009(Capotosto et al, , 2016(Capotosto et al, , 2012Marshall et al, 2015b). In addition, participants with stronger high-alpha phase synchronization exhibited a stronger behavioral benefit of visuospatial attention when detecting low-contrast but not high contrast stimuli in the right hemifield.…”
Section: Dynamic High-alpha Band Synchronization Connects Nodes Of Atmentioning
confidence: 65%
“…Participants who exhibited stronger high-alpha phase synchronization also exhibited stronger lateralization of low-alpha amplitudes during attention shifting. Highalpha phase synchronization between frontal and parietal cortices could thus mediate attention-related low-alpha band suppression, similar to structural connectivity (Marshall et al, 2015a) and perturbation of frontoparietal cortex with TMS (Capotosto et al, 2009(Capotosto et al, , 2016(Capotosto et al, , 2012Marshall et al, 2015b). In addition, participants with stronger high-alpha phase synchronization exhibited a stronger behavioral benefit of visuospatial attention when detecting low-contrast but not high contrast stimuli in the right hemifield.…”
Section: Dynamic High-alpha Band Synchronization Connects Nodes Of Atmentioning
confidence: 65%
“…Participants who exhibited stronger high-alpha phase synchronization also exhibited stronger lateralization of low-alpha amplitudes during attention shifting. High-alpha phase synchronization between frontal and parietal cortices could thus mediate attention-related low-alpha band suppression, similar to structural connectivity (Marshall et al, 2015a) and perturbation of frontoparietal cortex with TMS (Capotosto et al, 2009;Capotosto et al, 2016;Capotosto et al, 2012;Marshall et al, 2015b). In addition, participants with stronger high-alpha phase synchronization exhibited a stronger behavioral benefit of visuospatial attention when detecting low-contrast but not high contrast stimuli in the right hemifield.…”
Section: High-alpha Band Phase Synchronization Plays a Functional Rolmentioning
confidence: 66%
“…Causal support for a segregation of parietal regions that are involved in memory (albeit semantic) retrieval and perceptual attention comes from a recent study 35 that combined electroencephalography (EEG) with the inhibitory effect of repetitive transcranial magnetic stimulation 36,37 (rTMS) during task anticipation. We found that both performance and anticipatory desynchronization of oscillations in the alpha band were affected by stimulation of the pIPS only during the perceptual attention task and of the AG only during the semantic retrieval task, demonstrating a double dissociation between PPC regions and task demands.…”
Section: Attention and Episodic Retrievalmentioning
confidence: 99%